EVALUASI PROSES KEBIJAKAN PROGRAM NASIONAL PEMBERDAYAAN MASYARAKAT (PNPM) MANDIRI PERKOTAAN DI KELURAHAN GENUKSARI KECAMATAN GENUK KOTA SEMARANG - Eriyal Adhiyan Akhsani; Reni Windiani; Priyatno H (Journal of Politic and Government Studies, 2014)
This research aims to gain an overview and explanation of how the implementation and the role of BKM Mandiri PNPM Urban in community empowerment in Sub Genuksari Genuk District of the city, as well as any factors that may affect the implementation of community empowerment through the PNPM Urban . This type of research is descriptive qualitative , which is a type of research that can provide a factual overview of the implementation of community development programs to activities that include social , environmental , and revolving funds . Data collection is done by means of interviews , documentation and observation .In the face of obstacles that exist in the implementation , and village governments are working to resolve the BKM Self as much as possible . Barriers such as lack of budget allocation to improve performance , the concept of development is slow , and the lack of human resources community . For the problem of budget allocation , manager of BKM Mandiri has worked hard to generate profits through the revolving loan funds that flow from the city government can also be optimized . In addition BKM Mandiri also trying to approach the private sector to invest in order to create a good relationship between the government and the private sector in order to achieve public goals through the Public Private Partnership good . As for the lack of information received by the public , BKM Mandiri seeks to conduct coaching and training more intensively in order to improve the quality of human resources KSM .In the management of PNPM MP assessed no political factors that affect the performance of BKM Mandiri itself. In the management of PNPM MP preferred aspect is the aspect of profit ( profit- oriented) to reduce poverty rather than political aspects .Keyword : Evaluation, Policy, PNPM MP